Simultaneous melt and vapor induced ash deposit aging mechanisms – Mathematical model and experimental observations. (14th December 2017) - Niemi, Jonne; Lindberg, Daniel; Engblom, Markus; Hupa, Mikko
Graphical abstract: Highlights: Temperature gradient observed to affect microstructure and composition. Liquid-phase sintering recognized as responsible for deposit densification. Liquid-phase migration due to temperature gradient zone melting observed. Gas-phase alkali chloride migration towards colder temperatures observed and modeled. Abstract: A laboratory method was used to study the effects of temperature gradients on synthetic ash deposits consisting of KCl-K2 SO4 or NaCl-Na2 SO4 . The cross-sections of the deposits were analyzed using SEM/EDX. The deposits were observed to form multilayered morphologies, with porous inner layers and dense outer layers. In addition, the outer layer composition was homogenized. The densification and chemical homogenization occurred by liquid-phase sintering and by temperature gradient induced liquid-phase migration. Alkali chlorides were observed to migrate in the gas-phase towards the colder temperatures. The phenomenon was modeled and recognized to be temperature gradient induced Fickian gas-phase concentration diffusion. The migration rate is directly proportional to the temperature gradient and increases exponentially as a function of the absolute temperature. The microstructure of the particle of origin for the gaseous species was observed to function as a crucial limiting factor for the migration rate. The results show that temperature gradients affect the morphology and chemistry of ash deposits and induce alkali chloride migration towards the steel surface.